2011
DOI: 10.4102/sajhivmed.v12i2.194
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of pericardial diseases in HIV-positive patients at University College Hospital, Ibadan, Nigeria

Abstract: Rationale. Pericarditis has been reported as the most common cardiac complication of HIV disease, followed by pericardial effusion. Methods. A retrospective review was conducted of all 68 patients treated for pericardial diseases between August 2003 and July 2008 at University College Hospital, Ibadan, Nigeria. HIV-positive patients (N=42) were compared with those who were HIV negative (N=26). Results. More male than female patients presented with pericardial disease, and the HIV-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…This study shows a relatively high rate of HIV infection (32/83, 38.6%) among patients with constrictive pericarditis compared to the 14.6% reported by Mutyaba et al 2 in a recent South African study, but less than the 12/19 (63%) reported by Abubaker and colleagues 17 in a Nigerian study. These data for developing countries are in contrast to the very low rate reported by Gopaldas et al 18 in the USA, who found only 10 HIV-positive Data presented as mean ± standard deviation for continuous variables and n (%) for categorical variables.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…This study shows a relatively high rate of HIV infection (32/83, 38.6%) among patients with constrictive pericarditis compared to the 14.6% reported by Mutyaba et al 2 in a recent South African study, but less than the 12/19 (63%) reported by Abubaker and colleagues 17 in a Nigerian study. These data for developing countries are in contrast to the very low rate reported by Gopaldas et al 18 in the USA, who found only 10 HIV-positive Data presented as mean ± standard deviation for continuous variables and n (%) for categorical variables.…”
Section: Discussioncontrasting
confidence: 48%
“…2 Recent data suggest that co-existing HIV infection may modify the clinical manifestations and natural history of tuberculous pericarditis and resultant constriction. 17,18 Our study was designed to evaluate the clinical profile and surgical outcomes of HIV-positive and -negative patients with constrictive pericarditis.…”
mentioning
confidence: 99%
“…Two of our patient were HIV positive and they presented with massive effusion and were on antiretroviral and anti-tuberculous drugs at the time of presentation. The association between massive effusion in patients with tuberculosis and HIV infection has been reported [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a subset of pericardial disease known as effusive-constrictive pericarditis was stated as deserving a closer attention as treatment was challenging [7]. Also, one of the important causes of pericardial diseases resulting in HF in HIV-AIDS patients, that is amenable to surgery, is pericardial effusion [8]. Thus the duo of tuberculosis and HIV infections which are common in the sub-region, have made the condition of pericardial diseases common [9] [10].…”
Section: Epidemiologymentioning
confidence: 99%